Leaf and Canopy Traits Associated with Stay-Green Expression Are Closely Related to Yield Components of Wheat Genotypes with Contrasting Tolerance to Water Stress - Felipe Moraga; Marta Alcaíno; Iván Matus; Dalma Castillo; Alejandro del Pozo (Plants, 2022)
The onset and rate of senescence influence key agronomical traits, including grain yield (GY). Our objective was to assess the relationships between stay-green and GY in a set of fourteen spring bread wheat (Triticum aestivum L.) genotypes with contrasting tolerance to water stress. Based on leaf chlorophyll content index (Chl) and normalized vegetation index (NDVI) measurements, the senescence dynamics at leaf and canopy levels, respectively, were quantified. Parameters describing the dynamics of senescence were examined in glasshouse and field experiments under well-watered (WW) and water-limited (WL) regimes, and they included the following stay-green traits: maximum NDVI or Chl near to anthesis (NDVImax, Chlmax), the senescence rate (SR, rate), the area under curve (AreaNDVI, AreaChl), and the time from anthesis to 10 (tonset), 50 (t50, X50) and 90% (t90) senescence. Our results revealed that specific stay-green traits were significantly different among genotypes and water regimes in both glasshouse and field experiments. GY was positively correlated with ttotal (0.42), tonset (0.62) and NDVIdif (0.63). Under WL, NDVIdif and NDVImax correlated with GY (0.66–0.58), but only t50 correlated with GY under WW (0.62), indicating that phenotyping of stay-green trait is a useful tool for tracking the dynamics of senescence in WW and WL environments.